Performance evaluation of drip irrigation system in passion fruit cultivation (Research, Society and Development, 2021)
The constant evaluation of the performance of the irrigation systems is necessary to verify if the conditions foreseen in the project are consistent with the observed in the field. Thus, the objective was to evaluate the performance of localized irrigation systems in order to indicate uniformity measures. The work was carried out at Fazenda Areião, an experimental area of ESALQ/USP, Piracicaba/SP, cultivated with passion fruit. The evaluation was based on the following performance coefficients: Christiansen's uniformity coefficient (CUC), distribution uniformity coefficient (CUD), statistical uniformity coefficient (CUE) and application efficiency (Ea) of the volume distribution data of water obtained from field tests. In the present work, the results showed that CUC (89.86%), CUD (90.37%) and CUE (99.88%) are within the standards of performance classification of the emitters and the average application efficiency was 83.03 %, indicating that the performance evaluation of the drip irrigation system is in perfect operating condition.